تفعيل دور صناديق الاستثمار الاسلامية في تطوير نشاط المصارف الاسلامية ّدراسة حالة :عينة من صناديق الاسهم السعودية خلال الفترة (2017/2021). - سعد, رضواني; العيد, تركي; علي, تامة (University of eloued جامعة الوادي, 2021)
" تأتي هذه الدراسة في إطار الاهتمام بالدور الذي تؤديه الصناديق الاستثمارية الإسلامية في تطوير نشاط المصارف الإسلامية التابعة لها، حيث تعتبر الصناديق الاستثمارية عموما أحد أهم الأوعية الاستثمارية التي تقوم بجمع رؤوس أموال مجموعة من المستثمرين وإدارتها وفقا لإستراتيجية وأهداف استثمارية محددة محققة بذلك جملة من المميزات تجعلها أكثر جاذبية عن غيرها من الأدوات الاستثمارية، أما تأسيس الصناديق الاستثمارية المتوافقة مع المبادئ الشرعية كان حديثا بحيث يعود إلى سنوات قليلة ماضية وقد شهدت الفترة الأخيرة اهتماما بالغا وواسعا بهذه الأداة من قبل المصارف الإسلامية وحتى غير الإسلامية (سواء في الدول العربية أو الغربية) أين قامت بتأسيس وإدارة الصناديق الاستثمارية الإسلامية نظرا للإقبال الكبير عليها؛ وعلى هذا الأساس تمحورت هذه الدراسة حول الإجابة على إشكالية أساسية هي: كيف تساهم صناديق الاستثمار الإسلامية في تطوير نشاط المصارف الإسلامية؟ وتوصلنا من خلال هذه الدراسة إلى أن الصناديق الاستثمارية الإسلامية لها دور في تدعيم الاستثمار المصرفي الإسلامي في إطار المضاربة الشرعية وكذا في تدعيم الاستثمار طويل الأجل وحل مشكلة السيولة في المصارف الإسلامية، كما لها دور في تدعيم علاقة المصارف الإسلامية بالسوق المالي الإسلامي و توطيد المنافسة بينها وبين المصارف التقليدية، وهذا من أجل إبراز مختلف الجوانب منها النظرية و التطبيقية على التوالي بالإضافة إلى دراسة عينة من صناديق الإستثمار التي تخضع لضوابط الشريعة الإسلامية في السوق المالية السعودية خلال الفترة الممتدة من سنة 2017 حتى سنة 2021 وهذا بالاعتماد على البيانات و المعلومات المفصحة عنها من قبل الإدارة المشرفة على هذه الصناديق وتحليلها، من أجل إبراز مدى الكفاءة التي تتمتع بها الإدارة في مقابل ما هو مطلوب في المجال الخاص بتسيير صناديق الإستثمار الإسلامية. "" This study is concerned with the role played by Islamic investment funds in developing the activity of their Islamic banks, where investment funds considered generally one of the most important investment instrument that manage and collect the capitals of a group of investors according to a specific investment strategy and objectives thus leads to achieve a variety of advantages which make it more attractive than other investment instruments, as for the establishment of shariah-compliant investment funds was recently where it dates back to a few years ago, and the recent period has seen great and widespread interest in this tool by Islamic and even non-Islamic banks (whether in the Arab or western countries) where it has established and managed Islamic investment funds because of the high demand for them; on this basis, this study focused on the answer to a fundamental problem: How do Islamic investment funds contribute to the development of Islamic banking activities? Through this study, we have concluded that Islamic investment funds have a role in strengthening Islamic banking investment in the context of Sharia speculation as well as in strengthening long-term investment and solving the liquidity problem of Islamic banks, it also has a role in strengthening the relationship of Islamic banks to the Islamic financial market and strengthening competition between them and conventional banks. This is in order to highlight various aspects, including theoretical and applied, respectively, in addition to studying a sample of investment funds that are subject to Islamic law controls in the Saudi financial market during the period from 2017 to 2021, this is based on the data and information disclosed by the management overseeing these funds and analysis through ,to show the efficiency of the management in exchange for what is required in the field of the management of Islamic investment funds. "
ماستر اقتصاد
Keywords: صناديق الاستثمار، صناديق الاستثمار الإسلامية، المصارف الإسلامية، سوق الأسهم السعودي.; investment funds, Islamic investment funds, Islamic banks, the Saudi equity market